Knowledge, Attitude and Practices towards Management of Diarrhea among Care takers of Children below 5 years attending Katoogo Health Centre III, Mukono District. A Cross-sectional Study. - Ssebuliba, Julius; Nakasolo, Sania (Student’s Journal of Health Research Africa, 2022)
Background: The purpose of the study was to assess the knowledge, attitude, and practices towards the management of diarrhea among caretakers of children below five years attending Katoogo Health Centre III, Mukono district. The specific objectives of the study were to assess the; knowledge towards management of diarrhea among caretakers of children below five years, attitudes towards management of diarrhea among caretakers of children below five years, and practices towards management of diarrhea among caretakers of children below five years. Methodology: The study employed a descriptive cross-sectional design with a simple random sampling technique as a sampling technique. Data were extracted from a sample of 50 respondents using semi-structured questionnaires written in the English language and analyzed manually by use of tally sheets, entered in the excel computer program to generate tables, graphs, and pie charts. Results: Overall results on practices towards management of diarrhea showed that; (60%) of respondents’ children were not exclusively breastfed, (54%) of their children’s immunization cards were not up to date as per EPI guidelines, (and 58%) administered ORS to their children during an episode of diarrhea, (94%) keep solid wastes at home in open heap garbage places, (50%) sometimes they practice personal hygiene and (56%) visit the doctors when the child’s health does not improve. Conclusion: The researcher generally concluded that caretakers exhibited fairly pleasant knowledge and attitude towards management of diarrhea but poor practices were noticed which exposes their children to persistent diarrhea illness. Recommendation: The researcher, therefore, strongly recommended that Katoogo Health Centre III should intensively promote health education on diarrhea not only on what is all about but majorly preventive practices on the occurrence since prevention is better than cure.